MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DI SD NEGERI 018 RANTAU SIALANG KECAMATAN KUANTAN MUDIK - Arni Arni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research was motivated by the low level of mathematics learning outcomes of class III SD Negeri 018Rantau Sialang. The purpose of this study was to improve student mathematics learning outcomes. The design ofthis study uses classroom action research which consists of two cycles. From the data analysis in the first cycle,the percentage of teacher activity value was 66.6% in the good category and increased in the second meeting to75% in the good category. In the second cycle the first meeting the percentage of teacher activity was 83.3%very good and at the second meeting increased to 87.5% in the very good category. The percentage of studentactivity in the first cycle was 62.5% with good categories and at the second meeting increased to 70.8% withgood categories. In the second cycle of the first meeting the percentage of student activity was 87.5% in the verygood category and increased in the second meeting to 91.6% in the very good category. Student learningoutcomes in the baseline score of students completeness is 44.4%, completeness percentage in cycle I is 66.6%,and the percentage of completeness in cycle II is 88.8%. It can be concluded that by applying the cooperativelearning model type think pair share (TPS) can improve the mathematics learning outcomes of class III SDNegeri 018 Rantau Sialang